Adrenocortical carcinoma in pregnancy: A diagnostic dilemma - Ankush Jairath; Baldev S Aulakh (Indian Journal of Urology, 2014)
Adrenocortical carcinoma is a rare disease. Additionally, in the case of coexisting pregnancy, there are diagnostic difficulties due to associated physiological hormonal changes as well as imaging limitations. Cushing′s syndrome and virilization during pregnancy is a rare entity with few cases reported in the literature. Misdiagnosis is common as the syndrome may be easily confused with preeclampsia or gestational diabetes. We present the case of a 31-year-old pregnant woman with rapidly developing symptoms related to hormonally active adrenocortical cancer.